PEMBELAJARAN BAHASA INDONESIA DARING DAN EFEKTIVITASNYA DI MASA PANDEMI COVID-19 - Purwanto (LPPM STKIP PGRI Sidoarjo, 2021)
This study aims to describe the effectiveness of online Indonesian language (Bahasa Indonesia) learning that improves students’ language skills in the cognitive domain. The research method used was descriptive qualitative. The data were in the form of teacher and student reports about the learning process and documentation. Data collection techniques were done by observation, interview and questionnaire. The data analysis technique used interactivity. The results of the study were distinguished by three findings, namely the online learning process, learning obstacles and learning achievement based on the Minimum Completeness Criteria (KKM) obtained by students in the cognitive domain. Learning during the Cocid-19 pandemic takes place online. Obstacles had been found in learning, especially those faced by students. Learning Indonesian online by improving language skills in the cognitive aspect was effective. This was indicated by the achievement of students’ scores higher or above the average of the KKM (> 80).